Ghrelin and ghrelin receptor modulation of psychostimulant action - Wellman, Paul J.; Clifford, P S.; Rodriguez, Juan A. (Frontiers in Neuroscience, 2013)
Ghrelin (GHR) is an orexigenic gut peptide that modulates multiple homeostatic functions including gastric emptying, anxiety, stress, memory, feeding and reinforcement. GHR is known to bind and activate growth-hormone secretagogue receptors (termed GHR-Rs). Of interest to our laboratory has been the assessment of the impact of GHR modulation of the locomotor activation and reward/reinforcement properties of psychostimulants such as cocaine and nicotine. Systemic GHR infusions augment cocaine stimulated locomotion and conditioned place preference (CPP) in rats, as does food restriction which elevates plasma ghrelin levels. Ghrelin enhancement of psychostimulant function may occur owing to a direct action on mesolimbic dopamine function or may reflect an indirect action of ghrelin on glucocorticoid pathways. Genomic or pharmacological ablation of GHR-Rs attenuates the acute locomotor-enhancing effects of nicotine, cocaine, amphetamine and alcohol and blunts the CPP induced by food, alcohol, amphetamine and cocaine in mice. The stimulant nicotine can induce CPP and like amphetamine and cocaine, repeated administration of nicotine induces locomotor sensitization in rats. Inactivation of ghrelin circuit function in rats by injection of a ghrelin receptor antagonist (e.g. JMV 2959) diminishes the development of nicotine-induced locomotor sensitization. These results suggest a key permissive role for GHR-R activity for the induction of locomotor sensitization to nicotine. Our finding that GHR-R null rats exhibit diminished patterns of responding for intracranial self-stimulation complements an emerging literature implicating central GHR circuits in drug reward/reinforcement. Finally, antagonism of GHR-Rs may represent a smoking cessation modality that not only blocks nicotine-induced reward but that also may limit weight gain after smoking cessation.